Closing the gaps on the viral photosystem‐I psaDCAB gene organization. (14th October 2015) - Roitman, Sheila; Flores‐Uribe, José; Philosof, Alon; Knowles, Ben; Rohwer, Forest; Ignacio‐Espinoza, J. Cesar; Sullivan, Matthew B.; Cornejo‐Castillo, Francisco M.; Sánchez, Pablo; Acinas, Silvia G.; Dupont, Chris L.; Béjà, Oded
Summary: Marine photosynthesis is largely driven by cyanobacteria, namely Synechococcus and Prochlorococcus . Genes encoding for photosystem (PS) I and II reaction centre proteins are found in cyanophages and are believed to increase their fitness. Two viral PSI gene arrangements are known, psaJF→C→A→B→K→E→D and psaD→C→A→B . The shared genes between these gene cassettes and their encoded proteins are distinguished by %G + C and protein sequence respectively. The data on the psaD→C→A→B gene organization were reported from only two partial gene cassettes coming from Global Ocean Sampling stations in the Pacific and Indian oceans. Now we have extended our search to 370 marine stations from six metagenomic projects. Genes corresponding to both PSI gene arrangements were detected in the Pacific, Indian and Atlantic oceans, confined to a strip along the equator (30°N and 30°S). In addition, we found that the predicted structure of the viral PsaA protein from the psaD→C→A→B organization contains a lumenal loop conserved in PsaA proteins from Synechococcus, but is completely absent in viral PsaA proteins from the psaJF→C→A→B→K→E→D gene organization and most Prochlorococcus strains. This may indicate a co‐evolutionary scenario where cyanophages containing either of these gene organizations infect cyanobacterial ecotypes biogeographically restricted to the 30°N and 30°S equatorial strip.